2020
DOI: 10.21037/tcr.2020.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Positive lymph node ratio as a novel indicator of prognosis in gastric signet ring cell carcinoma: a population-based retrospective study

Abstract: Background Lymph node status has a strong predictive effect on the prognosis of all patients with gastric cancer. It is unclear whether the positive lymph node ratio (PLNR) is a reliable prognostic factor for gastric signet ring cell carcinoma (SRCC). Methods Patients with SRCC were obtained from the Surveillance, Epidemiology and End Results (SEER) database for the years 1998–2013. Cutoff values of positive lymph node ratio (PLNR) were decided using X-tile program. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, lymph node metastasis in GSRCC turned out to be non-FDG-avid type [ 30 ]. Another study indicated that positive lymph node ratio could be an alternative indicator in GSRCC as well [ 31 ]. Moreover, endoscopic ultrasound (EUS) is mentioned as one of the gold standards for detecting positive regional lymph nodes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymph node metastasis in GSRCC turned out to be non-FDG-avid type [ 30 ]. Another study indicated that positive lymph node ratio could be an alternative indicator in GSRCC as well [ 31 ]. Moreover, endoscopic ultrasound (EUS) is mentioned as one of the gold standards for detecting positive regional lymph nodes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%